DRYING CHARACTERISTICS OF SEA CUCUMBER (STICHOPUS JAPONICAS SELENKA) USING FAR INFRARED RADIATION DRYING AND HOT AIR DRYING - Moon, Ji Hoon; Kim, Moo Jung; Chung, Dong Hwa; Pan, Cheol-Ho; Yoon, Won Byong (WILEY, 2014)
Sea cucumber (Stichopus japonicus Selenka, SC) was dried using far infrared radiation drying (FIRD) and air drying (AD). The effect of the drying temperature of FIRD and AD on the drying rate of SC was investigated. Temperatures varied at 60, 70 and 80C, with a constant air velocity (13.2 m/s). Thin-layer drying models were applied to describe the drying process of SC with FIRD and AD. The Midilli and Kucuk equation showed the best fit (R-2 > 0.99). The effective moisture diffusivity (D-eff) was estimated by the diffusion model based on the Fick's second law. The D-eff values of FIRD and AD treated samples varied in the range of 3.39 10(-10) to 5.16 10(-10) m(2)/s and 2.81 x 10(-10) to 3.81 x 10(-10) m(2)/s, respectively. The activation energy (E-a) based on the drying temperature showed that the thermal sensitivity of FIRD was higher than that of AD. The scanning electron microscope images showed more damages on the surface of AD treated sample than that of FIRD.
Keywords: MOISTURE DIFFUSIVITY; QUALITY; KINETICS; BANANA; FRESH; MODEL